2013
DOI: 10.1002/jlcr.3083
|View full text |Cite
|
Sign up to set email alerts
|

A convergent stereocontrolled synthesis of [3‐14C]solanesol

Abstract: In this communication, we report the synthesis of ~5 mCi of [3-(14) C]solanesol (1) prepared from ethyl [3-(14) C]acetoacetate and (all-E)-octaprenyl bromide (2) in four steps, with a specific radioactivity of 19.83 mCi/mmol and with a chemical/stereochemical and radiochemical purity of ≥ 95%. (Figure ). Position 3 of the chain was selected for (14) C labelling because of the metabolic stability of this position. Unlabelled (all-E)-octaprenyl (18) (Scheme ) necessary for this work was prepared via a convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…After chemical synthesis, solanesol contains cis and trans structures; in contrast, solanesol derived from natural sources in plants contains only the trans Phytochem Rev structure with a and b forms (Roe et al 2013). X-ray diffraction study showed, a form was in one plane, and b form was folded (Stedman 1968).…”
Section: Existing Forms In Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…After chemical synthesis, solanesol contains cis and trans structures; in contrast, solanesol derived from natural sources in plants contains only the trans Phytochem Rev structure with a and b forms (Roe et al 2013). X-ray diffraction study showed, a form was in one plane, and b form was folded (Stedman 1968).…”
Section: Existing Forms In Plantsmentioning
confidence: 97%
“…While artificially synthesised solanesol contains both cis and trans structures, solanesol formed in plants contains only the trans structure (Roe et al 2013), and this should be considered when developing novel solanesol-based drugs. Solanesol has strong free radical absorption properties because of its nonconjugated double bonds; as a natural extract, solanesol is expected to have applications in the inhibition of skin aging and senile plaque formation (Bai et al 2014).…”
Section: Production Of New Drugsmentioning
confidence: 99%
“…Because the chemical synthesis of solanesol is difficult [11], we assessed some aspects of its biosynthesis in tobacco plants and observed differential accumulation of solanesol in the leaves, stems, and roots of tobacco plants, with the content in leaves being the highest (Figure 2A). Thus, tobacco leaves could be the ideal material for extracting solanesol [3,12].…”
Section: Solanesol Is Abundant In Tobacco Leavesmentioning
confidence: 99%
“…Solanesol exist in both cis and trans states, for this experiment we considered only trans as it is 122 only found in natural sources (Roe, Oldfield, Geach, & Baxter, 2013). The structure of Solanesol 123 was obtained from PubChem compound (CID 5477212) (Kim et al, 2015;NCBI 2016).…”
Section: Ligand Preparation 121mentioning
confidence: 99%